Beneath Bass Strait: linking Tasmania and mainland Australia using ambient seismic noise - Pilia, S; Rawlinson, N; Direen, N; Anya Reading (2013)
One of the most hotly debated topics in Australian geology pertains to the tectonic relationship between Tasmania and mainland Australia. The focus of this study is ambient seismic noise data from 24 broadband stations, which span northern Tasmania, several islands in Bass Strait (King Island, Deal Island and Flinders Island) and southern Victoria, thus providing a dense coverage of surface wave paths that can be exploited to image the 3-D structure of the crust joining Tasmania and Victoria in high detail. The new results of this study will address fundamental questions regarding Tasmania’s tectonic provenance and its enigmatic relationship with the mainland. Furthermore, they will impose important constraints on the broad scale geology of a highly prospective region that hosts significant hydrocarbon deposits. To produce the highest quality Green’s functions, careful processing of the data has been performed, after which group and phase velocity dispersion measurements have been carried out using a frequency-time analysis method on the symmetric component (average of the casual and acasual signal) of the empirical Green’s functions (EGFs). The location of the experiment is such that the cross-correlations produce strong signal down to 1s period, thanks to the proximity of microseisms in Bass Strait and the Southern Ocean. Group and phase dispersion measurements from the EGFs have been inverted to obtain Rayleigh-wave group and phase velocity maps at different periods, which are expected to shed new light on the structure beneath Bass Strait.